A two-dimensional perovskite oxyfluoride Pb3Fe2O5F2 as a catalyst for electrochemical oxidation of water to oxygen. Issue 10 (19th April 2022) - Mizuochi, Ryusuke; Oka, Kengo; Inaguma, Yoshiyuki; Maeda, Kazuhiko
Abstract : A two-dimensional layered perovskite oxyfluoride Pb3 Fe2 O5 F2 has electrocatalytic activity for water oxidation and showed nearly 8-fold more evolved O2 than a three-dimensional bulk PbFeO2 F. Abstract : A two-dimensional (2D) perovskite oxyfluoride Pb3 Fe2 O5 F2, deposited on a conductive glass substrate, exhibited activity for electrochemical oxidation of water. This 2D oxyfluoride electrode could oxidize water forming O2 at a relatively low potential of +1.7 V vs. RHE with a faradaic efficiency of almost unity; the O2 evolution activity was nearly 8-fold higher compared to that for a 3D bulk PbFeO2 F analogue prepared in a similar manner.